1992
DOI: 10.1104/pp.100.4.1878
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fluxes in Mature Peach Leaves

Abstract: The turnover and transport of sugars are described in peach (Prunus persica L. Batsch), a species exporting both sucrose and sorbitol. Apparent export rate was slower in peach leaves than in leaves of herbaceous species. Sorbitol was the major soluble end product of photosynthesis and the major soluble carbohydrate in the leaf (higher than sucrose). Carbon fluxes were described using 14C labeling, radioactivity loss curves, and compartmental analysis during the second half of the photoperiod when chemical stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 26 publications
2
68
0
3
Order By: Relevance
“…Although expected because hexitols such as mannitol (Davis and Loescher, 1990;Flora and Madore, 1993;Flora and Madore, 1996) and sorbitol (Moing et al, 1992(Moing et al, , 1997 have been shown to be important phloem-mobile carbohydrates, no heptitols have actually been demonstrated to play the same role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although expected because hexitols such as mannitol (Davis and Loescher, 1990;Flora and Madore, 1993;Flora and Madore, 1996) and sorbitol (Moing et al, 1992(Moing et al, , 1997 have been shown to be important phloem-mobile carbohydrates, no heptitols have actually been demonstrated to play the same role.…”
Section: Discussionmentioning
confidence: 99%
“…One exception might be galactitol, which was suggested to be formed directly from unphosphorylated Gal (and NADPH) (Negm, 1986). Although all foliar alditols are thought to be phloem-mobile (Lewis, 1984), this has only been demonstrated for sorbitol, mannitol, and galactitol (Zimmermann and Ziegler, 1975;Davis and Loescher, 1990;Moing et al, 1992;Flora and Madore, 1993).…”
mentioning
confidence: 99%
“…Le plus souvent, les polyols, de même que le saccharose, sont très rapidement marqués, ce qui indique qu'ils sont issus directement de l'activité photosynthétique. C'est le cas du sorbitol (Anderson et al, 1961 ;Bieleski et Redgwell, 1985 ;Gaudillère et al, 1991 ;Escobar-Gutiérrez, 1995), du mannitol (Rumpho et al, 1983 ;Davis et al, 1988 ;Davis et Loescher, 1990 ;Loescher et al, 1992), de l'allitol et du volemitol (Bieleski, 1982 (Gaudillère et al, 1991 ;Moing et al, 1992 ;Escobar-Gutiérrez, 1995).…”
Section: Métabolismeunclassified
“…The bark tissue was cold extracted from the shoots with a sharp scalpel. After taking fresh weights, the tissues were frozen, lyophilized, grounded and stored at -40º C. The carbohydrate determination procedures were base on the Moing et al (1992) and Mehouachi et al (1995) methodology, as follows: Soluble sugar was extracted three times from 100 mg ground samples, using 80% hot ethanol. The residue was washed with mQ water three times.…”
Section: Measurements Of Carbohydratesmentioning
confidence: 99%
“…The carbohydrates were extracted according to the procedure described by Moing et al (1992) and Mehouachi et al (1995). Soluble sugars were extracted from powdered samples (100 mg dry wt) with 1.0 ml of 80% ethanol.…”
Section: Analysis Of Carbohydratesmentioning
confidence: 99%